Civil commitment for opioid misuse: do short-term benefits outweigh long-term harms? - Messinger, John C. (Journal of medical ethics, 2022)
In response to a sharp rise in opioid-involved overdose deaths in the USA, states have deployed increasingly aggressive strategies to limit the loss of life, including civil commitment—the forcible detention of individuals whose opioid use presents a clear and convincing danger to themselves or others. While civil commitment often succeeds in providing short-term protection from overdose, emerging evidence suggests that it may be associated with long-term harms, including heightened risk of severe withdrawal, relapse and opioid-involved mortality. To better assess and mitigate these harms, states should collect more robust data on long-term health outcomes, decriminalise proceedings and stays, provide access to medications for opioid use disorder and strengthen post-release coordination of community-based treatment.